1991
DOI: 10.1099/00221287-137-7-1701
|View full text |Cite
|
Sign up to set email alerts
|

Induction of increased thermotolerance in Saccharomyces cerevisiae may be triggered by a mechanism involving intracellular pH

Abstract: Incubation of Saccharomyces cerevisiae at sub-lethal temperatures results in an increase in thermotolerance. This process is dependent not only on the sub-lethal temperature but also on the duration of sub-lethal heating. This indicates that the mechanism inducing thermotolerance is a timeltemperature dose response. Other factors that induce thermotolerance include exposure to ethanol, sorbic acid and low external pH values. These factors induce thermotolerance after incubation in the presence of protein synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 42 publications
4
73
0
2
Order By: Relevance
“…It is difficult to assess this study as the conditions, notably pH, of growth were not reported. Coote et al (1991) showed thermotolerance increasing during a 9 mM sorbic acid treatment, both at pH 4.5 and at pH 6.0. However, a partial thermotolerance increase was also seen in cells exposed to pH 4-5 in the absence of sorbate.…”
Section: The Effects Of Sorbate On Thermotolerancementioning
confidence: 99%
“…It is difficult to assess this study as the conditions, notably pH, of growth were not reported. Coote et al (1991) showed thermotolerance increasing during a 9 mM sorbic acid treatment, both at pH 4.5 and at pH 6.0. However, a partial thermotolerance increase was also seen in cells exposed to pH 4-5 in the absence of sorbate.…”
Section: The Effects Of Sorbate On Thermotolerancementioning
confidence: 99%
“…These include an increase in membrane permeability and passive proton influx, and a dissipation of the proton motive force across the plasma membrane. The level of the plasma membrane H + -ATPase declines following exposure to ethanol or heat, but the activity of the residual enzyme increases dramatically (Coote et al, 1991(Coote et al, , 1994Rosa and Sá-Correia, 1991;Monteiro and Sá-Correia, 1998;Piper et al, 1994). Consequently, more ATP is spent by the cells in response to ethanol stress or heat shock.…”
Section: Introductionmentioning
confidence: 99%
“…Adapted cells are not only able to resume growth, but are also more protected when exposed to a new stress situation (Trollmo et al, 1988;Varela et al, 1992). This protection is not only limited to a second challenge of the same kind of stress, but also to other types of stress, indicating that the stress response consists of both specific and general elements (Coote et al, 1991;Trollmo et al, 1988;Varela et al, 1992).…”
Section: Introductionmentioning
confidence: 99%